FAKTOR PENYEBAB RENDAHNYA NILAI SOSIOLOGI SISWA DI SMA NEGERI I BONJOL KECAMATAN BONJOL KABUPATEN PASAMAN - Zulfitri, Linda; Maihasni, Maihasni; Elvawati, Elvawati (Pendidikan Sosiologi, 2013)
In this reseach, the reseacher used structuration Giddens theory, with internal and external factor to compel the people to do something. The approach used in this research was qualitative method with descriptive type to describe the detail in research.In colecting the data, the reseacher used observation and interview. The informant of the research with purposive sampling. The unit of the data analysis was people, with some stap. Collecting the data, reduction the data or analyzing the data, verification and conclusion.Based on the result of the research, the cause of lower score of sociology students in Senior High School I Bonjol was internal and external factor. Internal factor like: 1) lack of students attention in learning process, 2) lack of students motivation in learning process, 3) lack of students readness in learning processmain while, external factor sich as: 1) lack of parents participation, 2) lack of clear rule, 3) lack of facilities and infrastructure, 4) teacher method not interesting.